Association of patient-rated severity with other outcomes in patients with painful diabetic peripheral neuropathy - Taylor-Stokes G (Dove Medical Press, 2011)
Gavin Taylor-Stokes1, James Pike1, Alesia Sadosky2, Arthi Chandran2, Thomas Toelle31Adelphi Real World, Adelphi Mill, Bollington, Macclesfield, Cheshire, UK; 2Pfizer Inc, New York, NY, USA; 3Department of Neurology, Technische Universität München, Munich, GermanyObjective: To evaluate the association of patient-reported severity of painful diabetic peripheral neuropathy (pDPN) with other outcomes in a European population of patients using the Adelphi Disease Specific Programme for pDPN (DSP III, 2008).Methods: The severity of patients' pDPN (mild, moderate, or severe) was rated independently by both patients and physicians. Relationships were evaluated between patient-reported pDPN severity and other patient-reported outcomes including pain, sleep, function, and work productivity. Physicians rated the severity of patients’ pDPN (1 = mild, 2 = moderate, 3 = severe) and sleep interference.Results: Patient-reported data were available from 634 individuals (56.2% male, mean age 63 years) from France, Germany, Italy, and the UK, of whom only 22.2% reported that they were currently employed. pDPN severity was rated as mild, moderate, and severe by 22.2%, 60.9%, and 16.9% of the patients, respectively. There was a significant association between patient-rated and physician-rated pDPN severity (P < 0.0001), although there were discrepancies in agreement (kappa = 0.37, 95% confidence interval [CI] 0.31, 0.43; weighted kappa = 0.43, 95% CI 0.37, 0.48) among physician and patient ratings in a substantial proportion of patients across severity categories. Higher pDPN severity was associated with greater interference of daily function including sleep (P < 0.0001 for all pairwise comparisons). Among employed patients, percent of pDPN-related impairment while at work (presenteeism) and overall work impairment increased with greater pDPN severity, resulting in indirect costs that increased significantly with pDPN severity; $8266, $15,449, and $24,300 for mild, moderate, and severe pDPN, respectively (overall P < 0.001).Conclusion: Severity of patient-rated pDPN was significantly associated with outcomes, including function and productivity; poorer function and lower productivity were reported at higher pDPN severity levels. Moreover, physicians rated pDPN severity different from patients in a substantial proportion of patients.Keywords: diabetic neuropathy, pain, outcomes